Contingent Liabilities : A Threat to Fiscal Stability - Polackova, Hana (World Bank, Washington, DC, 2012)
The economic policy note discusses the issue of serious fiscal instability faced by many governments as a result of their contingent liabilities, which are associated with major hidden fiscal risks. Direct liabilities are predictable obligations that will arise in any event, and are the main subject of conventional fiscal analysis. Conversely, contingent liabilities are obligations triggered by a discreet but uncertain event, and are not always accounted for fully. The note further discusses explicit and implicit liabilities of a central government, suggesting ways to reduce fiscal risks for the policy makers.